2016
DOI: 10.1016/j.ccell.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Mdm2-RNA Interactions as a Target for Cancer Therapy: It’s Not All About p53

Abstract: In this issue of Cancer Cell, Gu et al. characterize small molecules that inhibit the interaction of Mdm2 with the mRNA that encodes the anti-apoptotic XIAP, simultaneously decreasing expression of both proteins. This represents a novel approach that has relevance in tumor cells independent of p53 status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Most patents for MDM2 antagonists concern small molecule inhibitors, e.g., Nutlin-3a and RG7112. Some of these molecules are currently under phases I, II and III of clinical trials (Li and Lozano, 2013;Bohlman and Manfredi, 2016;Burgess et al, 2016). Since cardiovascular side effects of anti-cancer therapies are a recurrent problem (Jain et al, 2017), characterizing the cardiovascular function of MDM2 has become a pressing issue.…”
Section: Introductionmentioning
confidence: 99%
“…Most patents for MDM2 antagonists concern small molecule inhibitors, e.g., Nutlin-3a and RG7112. Some of these molecules are currently under phases I, II and III of clinical trials (Li and Lozano, 2013;Bohlman and Manfredi, 2016;Burgess et al, 2016). Since cardiovascular side effects of anti-cancer therapies are a recurrent problem (Jain et al, 2017), characterizing the cardiovascular function of MDM2 has become a pressing issue.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified E3 ubiquitin ligase MDM2 as a novel therapeutic target in cervical cancer, unveiling a great treatment opportunity for cervical cancer patients [4,[19][20][21][22][23]. MDM2, known as Murine double minute 2, is known to be a negative regulator of p53 tumor suppressor gene [22].…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy is to target MDM2 and its interaction with mRNA that encodes the X-linked inhibitor of apoptosis protein (XIAP) [ 122 ]. Binding of the MDM2 protein to the internal ribosome entry site (IRES) on the mRNA encoding the anti-apoptotic XIAP results in stabilization of MDM2 protein and increased translation of XIAP [ 123 ]. This regulatory mechanism is not dependent on p53 status, and the ability to modulate two independent pathways by disrupting a single interaction could be a benefit of this novel therapeutic approach [ 123 ].…”
Section: Therapeutic Considerations and Conclusionmentioning
confidence: 99%
“…Binding of the MDM2 protein to the internal ribosome entry site (IRES) on the mRNA encoding the anti-apoptotic XIAP results in stabilization of MDM2 protein and increased translation of XIAP [ 123 ]. This regulatory mechanism is not dependent on p53 status, and the ability to modulate two independent pathways by disrupting a single interaction could be a benefit of this novel therapeutic approach [ 123 ]. Using a fluorescence polarization assay for high throughput screening of chemical libraries, Gu et al identified a panel of inhibitors that block protein-RNA interaction (MDM2-XIAP) leading to MDM2 degradation [ 122 ].…”
Section: Therapeutic Considerations and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation